2018
DOI: 10.1142/s0217590817440039
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Inclusion, Time Preference and Stock Investment of the Chinese Households

Abstract: Using the China Household Finance Survey data in 2011, the estimation results of structural equation modeling demonstrate that the respondents with higher time preference rate have a significant higher probability of investing in stocks, which implies that the short-term households will prefer stock investment. The social insurance programs and insurance policies held by the family will have a significantly direct positive effect in promoting stock investment and also a significantly direct positive effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…For the originally risk-seeking families, their risk asset investments are squeezed out; but for the originally risk-adverse families, their risk-free asset investments are squeezed out. Therefore, the direction of this study is consistent with the conclusion put forward by Yang and Wang ( 32 ): that China's social security system is mainly manifested as crowding-out residents' consumption and investment before it is highly improved.…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 87%
See 1 more Smart Citation
“…For the originally risk-seeking families, their risk asset investments are squeezed out; but for the originally risk-adverse families, their risk-free asset investments are squeezed out. Therefore, the direction of this study is consistent with the conclusion put forward by Yang and Wang ( 32 ): that China's social security system is mainly manifested as crowding-out residents' consumption and investment before it is highly improved.…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 87%
“…Some research on families' "limited participation" in the financial market are based on other perspectives besides background risk: one of which is that preventive saving has a negative effect on the allocation of risky financial assets by promoting households to accumulate more liquid riskfree assets and reducing financial risk exposure (30). China's family investment presents certain life cycle effect characteristics; however, the performance of different kinds of financial assets is inconsistent (31)(32)(33) concluded that the proportion of the elderly population has a positive effect on the holding of riskfree assets, represented by bank savings, and a negative impact on the holding of risk-free assets, represented by stocks, to a certain extent by further subdividing age groups. The above scholars' achievements further improve the research system of families' "limited participation" in the financial market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The structural model represents the relationship between latent variables, while the measurement model describes the relationship between latent variables and observe variables. According to the previous literature, in the structural equation model constructed, the control variables as explicit variables can not be brought into the model, and the relationship between latent variables should be focused on [97][98][99][100]. More variables will be introduced to the model when the robustness test is carried out.…”
Section: Basic Modelmentioning
confidence: 99%